Development and implementation of a conceptual survey in thermodynamics - Wattanakasiwich,P. (University of Sydney, 2015)
Thermodynamics is a basic topic for both science and engineering disciplines. There have been many studies on heat and temperature, but only few focused on laws of thermodynamics. This research aims to develop a conceptual survey for assessing student understanding of fundamental principles in thermodynamics. The construction of the survey is based on previous physics education research studies, in order to shorten the process of conceptual survey construction. The final version called the Thermodynamic Concept Survey (TCS) has both Thai and English versions and is divided into two parts-Part I consists of temperature and heat transfer, and ideal gas law and Part II consists of the first law of thermodynamics and processes. The content validity was analyzed by both Thai and Australian physicists. The reliability of the survey was determined by using more than 2,000 student responses from Australia and Thailand. The statistical analyses showed that the survey is reliable and valid. We also report on the implementation of the survey to investigate alternative conceptions in thermodynamics. We find that students did better on the earlier set of questions than the latter which involved integration of concepts. Ranges of understanding from the extant literature have been used to explore student answers.